Model updating of strategic building structures under real earthquake loading - Ceravolo, Rosario; Matta, Emiliano; Quattrone, Antonino; Zanotti Fragonara, Luca; De Stefano, Alessandro (CRC Press, 2013)
Public buildings such as hospitals, schools, churches and city halls constitute an asset of strategic importance into the life of a community. The assessment of the safety conditions and the vulnerability to natural catastrophic events must be checked, also resorting to experimental techniques. The adoption of vibration monitoring procedures represents a particularly appealing perspective for existing structures. The growing use of permanent monitoring systems allows collecting data of the structural response during earthquakes. An invaluable tool for structural health monitoring and damage detection, parametric system identification through model-updating is an inverse problem, affected by several kinds of modelling assumptions and measurement errors. By minimizing the discrepancy between the measured data and the simulated response, traditional model-updating techniques identify one single optimal model that behaves similarly to the real structure.